cGAS-dependent proinflammatory and immune homeostatic effects of the microtubule-targeting agent paclitaxel - Serpico, Angela Flavia; Pisauro, Caterina; Grieco, Domenico (Frontiers in Immunology, 2023)
Taxanes are Microtubule-Targeting Agents (MTAs) that exert potent anticancer activity by directly killing cancer cells. However, recent evidence suggests that they may also stimulate inflammation and anticancer adaptive immunity and that these actions strongly contribute to their therapeutic efficacy. Details on how Taxanes may modulate inflammation and anticancer immunity are, nevertheless, still missing. We show here that at very low doses the Taxane Paclitaxel (Pxl) indeed induces a potent proinflammatory response in various cancer cell types in a cyclic GMP-AMP (cGAMP) synthase (cGAS)- and Stimulator of Interferon Genes (STING)-dependent manner, leading to interferon (IFN) signaling. However, we find that Pxl treatment also strongly upregulates the expression of the immune checkpoint protein Programmed Death-Ligand 1 (PD-L1) in cancer cells, therefore, inducing an inhibitory response to adaptive immunity potentially attenuating anticancer immunity and therapeutic success. These observations provide a mechanistic explanation of why clinical benefit may derive from the combination of Pxl with Immune Checkpoint Inhibitors (ICIs) and suggest that more accurately tailoring dosage and schedule of this combination therapy may provide benefit in the management of a larger number of cancer types and stages.